The systematic status of Afropisa sanctaehelenae (Chace, 1966) (Decapoda, Brachyura, Majoidea, Epialtidae): morphological and molecular evidence - Isabel Muñoz; Paul F. Clark; Jose A. Cuesta (ZooKeys, 2025)
Afropisa sanctaehelenae (Chace, 1966) was originally described from three specimens collected from Saint Helena Island, South Atlantic, and assigned to Pisa Leach, 1814. It is a poorly known species, and until now, no new records have been reported. Recently, this species was transferred to a new genus, Afropisa Muñoz, García-Raso, González, Lopes, dos Santos & Cuesta, 2023, based exclusively on morphology. Nearly 60 years on from the original description, another eight specimens of A. sanctaehelenae have been made available for further study and sequencing. Mitochondrial 16S rRNA and cytochrome c oxidase subunit I sequences confirm the assignment of this Chace species to Afropisa. Photographs of the male holotype and female paratype confirmed the presence of additional characters; consequently, the present work provides a redescription of this species.